Size effects of micrometer-scaled metals—the search continues for materials containing real microstructures. (9th April 2017) - Ngan, A. H. W.; Chen, X. X.; Leung, P. S. S.; Gu, R.; Gan, K. F.
Abstract: Abstract : Recent observations on strength and deformation of small metals containing microstructures, including dislocation patterns, grain boundaries, and second-phase precipitates are reviewed. These microstructures impose an internal length scale that may interplay with the extrinsic length scale due to the specimen size to affect strength and deformation in an intricate manner. For micro-crystals containing pre-existing dislocations, Taylor work-hardening may dictate the dependence of strength on specimen size. The presence of grain boundaries in a small specimen may lead to effects far from the conventional Hall–Petch behavior. Precipitate–dislocation interactions in a small specimen may lead to an interesting weakest-size behavior.